Birds of a feather: the geographic interconnection of Australian universities on Twitter. (1st February 2016) - Palmer, Stuart
Abstract : Purpose: – Regardless of their virtual nature, research suggests that social media networks are still influenced by geography. The purpose of this paper is to investigate the connections between Australian universities on the Twitter social media system. Design/methodology/approach: – This research employs network analysis and visualisation to characterise the connections between Australian universities on Twitter. Findings: – A strong relationship to geography, both at the intra-state level and the inter-state level, was observed in the connections between Australian universities on Twitter. A relationship between number of followers and time since joining Twitter was also observed. Research limitations/implications: – The research presented is limited to Australian universities only and represents a snapshot in time only. Practical implications: – Australian universities have the opportunity to reach beyond the geographically restricted connections observed here, to actively seek new audiences, and to realise the cited benefits of online social media relating to increased connection across physical and digital frontiers. By capitalising on the strong "locality" observed in social media connections, a university could become a desirable source of information that is likely to be of interest to, and valued by, local constituents. Originality/value: – This paper contributes to the research literature on university use of social media by addressing the so far largely silent area of inter-institutional connections via social media, and the influence of physical geography on the connections between universities on Twitter. It also offers a practical methodology for those interested in further research in this area.